Design and Comparison of Microstrip Patch Antennas for Wireless Body Area Network - Krishna Veni, S; S K Gayatridevi, G (International Journal of Engineering and Technology, 2018)
The Body Area Network (BAN) is a wireless technology in combination with wearables. It is a monitoring system which is mainly used in health care, children tracking, in car-assistance and sports science etc. Â For wireless monitoring and continuous data transfer, an antenna needs to be integrated with the Body Area Network. This paper explains the different designs of microstrip patch antennas which operates at 2.4GHz and are more suitable for BAN. The simulation results in terms of return loss, gain and radiation pattern are presented.Â Â
Keywords: Body Area Network; HFSS; microstrip.